تأثير الجسم الأصفر على مردودية البييضات الصالحة للتطور In vitro عند الأبقار المحلية - جبور, زهير إبراهيم (Latakia University Journal -Biological Sciences Series, 2014)
الهدف من هذا البحث تحديد تأثير الجسم الأصفر في مراحله المختلفة على الخصائص الشكلية للمعقّد الخلوي )خلايا ركامية-بييضة)، وبالتالي على مردودية البييضات الصالحة شكلياً للتطوّر المختبري In vitro . جمعت البييضات من مبايض الأبقار بعد الذبح ، وقسّمت المبيايض إلى أربع مجموعات : آ- مبايض مع جسم نزفي . ب- مبايض مع جسم أصفر نشط وظيفياً . ج- مبايض مع جسم أصفر متراجع . د – مبايض بدون جسم أصفر . بينت النتائج في هذا البحث أنّ مردودية البييضات الصالح للتطوّر المختبري اختلفت وفقا لمرحلة الطور الأصفري . وكانت أعلى قيمة للمردودية في المبايض التي لاتحتوي جسما ًأصفراً ( 1.6±8.1 ) ، بينما أقلها في مرحلة الجسم الأصفر المتراجع، إذ بلغت (1.3±5.5). وقد كان الفرق معنوياً p < 0.001)) The purpose of this research was to determine the effect of the corpus luteum in various stages on morphological characteristics of cumulus oocyte complex consequently on the yield of morphologically intact oocytes for in vitro culturing. Oocytes were collected from cow ovariesof animals after slaughter. Ovaries were divided into the following four groups: (a) ovaries with corpus hemorrhagicum; (b) ovaries with a functional corpus luteum; (c) ovaries with regressing corpus luteum (albicans) ;( d) ovaries without any luteal structure. The results of this research show that, the intact oocytes yield for in vitro culturing differs accordingly with the stage of the corpus luteum. The highest percentage of intact cell(8.1 ± 1.6) were recorded in ovaries without corpus luteum , whereas the lowest percentage of intact cells were recorded in ovaries with regressing corpus luteum(5.5 ± 1.3). There was significant difference (p < 0.001)between the two groups for intact cells.